Importance of national and international registries of inborn errors of metabolism - Roberto Giugliani (Instituto Nacional de Pediatría, 2014)
In the subject of rare diseases, experience and knowledge is limited. With a rare disease registry, longitudinal data can be added to increase information of them and to improve the quality of medical care and the patient outcome. Registries, unlike randomized controlled trials, provide a source of real-time information to develop guidelines for monitoring and to support patient management. Registries are essential to show the real situation of rare diseases and to establish management goals in order to address the unmet needs of the patients.